Combining CDP-choline and galantamine: Effects of a selective α7 nicotinic acetylcholine receptor agonist strategy on P50 sensory gating of speech sounds in healthy volunteers. (June 2019) - Choueiry, Joelle; Blais, Crystal M; Shah, Dhrasti; Smith, Dylan; Fisher, Derek; Illivitsky, Vadim; Knott, Verner
Background: Schizophrenia (SCZ) patients and relatives have deficits in early cortical sensory gating (SG) typically measured by suppression of electroencephalography-derived P50 event-related potentials (ERPs) in a conditioning-testing (S1 –S2 ) paradigm. Associated with alpha 7 nicotinic acetylcholine receptor (α7 nAChR) dysfunction and shown to be improved with nicotine and α7 nAChR agonists, SG has recently been shown to be improved in low P50 suppressing SCZ patients following acute CDP-choline treatment. Aims: This pilot study in healthy humans assessed the SG effects of an α7 nAChR strategy combining CDP-choline with galantamine, a positive allosteric modulator (PAM) of nAChRs, aimed at increasing and prolonging nicotinic receptor activity. Methods: The combined effect of CDP-choline (500 mg) and galantamine (16 mg) on speech P50 gating indices rP50 (S2 /S1 ) and dP50 (S1 –S2 ) was examined in 30 healthy participants stratified into low and high baseline P50 suppressors in a randomized, double-blind, placebo-controlled and counterbalanced design. Results: In low suppressors, CDP-choline/galantamine (vs. placebo) improved rP50 and dP50 gating, and reduced S2 P50 amplitudes. No P50 gating effects were observed in high suppressors; however, CDP-choline/galantamine (vs. placebo) increased their S2 P50 amplitudes. Conclusion: Findings from this pilot study with CDP-choline/galantamine in a healthy, SCZ-like surrogate deficient gating sample are consistent with the association of α7 nAChR mechanisms in SG impairment in SCZ and support further research trials with CDP-choline and galantamine targeting sensory processes.